2019
DOI: 10.1021/acs.jafc.9b03520
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Peptide-Bound Maillard Reaction Products in Gastrointestinal Digests of Glyoxal-Glycated Casein by Human Colonic Microbiota

Abstract: A large portion of Maillard reaction products (MRPs) cannot be absorbed in the upper gut and therefore may be further decomposed and utilized by colonic microbiota (CM). This work reported the stability of UV-absorbent MRPs, fluorescent MRPs and peptide-bound N(ε)-(carboxymethyl)-lysine (CML) in high molecular weight (HMW, >10 kDa), medium molecular weight (MMW, 1−10 kDa), and low molecular weight (LMW, <1 kDa) gastrointestinal digests of glyoxalglycated casein in the presence of CM. Fluorescent MRPs showed hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…Through incubation of glycated proteins with fecal samples from healthy individuals, the relative amounts of intestinal microbiota, primarily Firmicutes and BacteroidetesI , was modulated at varying degrees (Helou et al., 2015; Xu et al., 2019; Yang et al., 2018). In rodent models fed with heat‐processed foods, an expansion in Firmicutes and a contraction in Bacteroidetes were observed (Marungruang, Fåk, & Tareke, 2016; Zhang & Li, 2018).…”
Section: Health Implications Of Dages: Perspectives To Fill the Gap Bmentioning
confidence: 99%
“…Through incubation of glycated proteins with fecal samples from healthy individuals, the relative amounts of intestinal microbiota, primarily Firmicutes and BacteroidetesI , was modulated at varying degrees (Helou et al., 2015; Xu et al., 2019; Yang et al., 2018). In rodent models fed with heat‐processed foods, an expansion in Firmicutes and a contraction in Bacteroidetes were observed (Marungruang, Fåk, & Tareke, 2016; Zhang & Li, 2018).…”
Section: Health Implications Of Dages: Perspectives To Fill the Gap Bmentioning
confidence: 99%
“…Based on the available literature, the human colonic microbiota seems to be capable of only fermenting LMW dAGEs and not the more complex HMW structures, including dAGEs and melanoidins. Xu et al (2019) subjected glyoxal-glycated casein to static in vitro digestion and assessed the capability of human colonic microbiota to ferment these digested compounds [56]. Their results showed that human colonic microbiota was indeed able to ferment the LMW structures to a better extent than HMW structures.…”
Section: Degradation and Effect In The Colonmentioning
confidence: 99%
“…Future studies will comprise detailed long-term studies to identify if rats on MRP rich diets will develop hypersensitivity or metabolic disorders as well as short-term studies to reveal the dynamics of the early MRP-induced changes in thymus and pancreas, and measurements of circulating GLP-1. In addition, it needs to be considered that degradation by the intestinal microbiota of dietary MRPs generates a lower amount of short chain fatty acids, as compared to control diets low in MRP 22 . This might cause dysbiosis and defect signaling between intestinal endocrine cells, immune cells, and gut microbiota.…”
Section: Discussionmentioning
confidence: 99%